THU0506 LONG-TERM EFFECTIVENESS AND SAFETY OF CANAKINUMAB AS A SECOND BIOLOGIC AFTER TOCILIZUMAB IN CHILDREN WITH EARLY AND LATE JIA WITH ACTIVE SYSTEMIC FEATURES. (2nd June 2020) - Alexeeva, E.; Krekhova, E.; Dvoryakovskaya, T.; Isaeva, K.; Chomakhidze, A.; Chistyakova, E.; Lomakina, O.; Denisova, R.; Mamutova, A.; Fetisova, A.; Gautier, M.; Vankova, D.; et al.
Abstract : Background: Canakinumab (CAN) is often used as second biologics in juvenile idiopathic arthritis with active systemic features (sJIA). However, there are little information about its long-term efficacy and safety. Objectives: To evaluate the long-term effectiveness and safety of CAN as a second biologics after tocilizumab (TOC) in sJIA patients depending on the duration of the disease. Methods: Thirty-one patients were enrolled in this study: the group of early sJIA (with duration shorter than 2 years, 19 patients) and the group of late sJIA (with duration longer than 2 years, 12 patients). At the baseline, information was collected on the characteristics of the onset of the disease, previous therapy and its success. At each visit at least 1 time per year clinical and laboratory characteristics of sJIA severity were assessed. Response to therapy was assessed using the ACRPedi 30/50/70/90 criteria and the C.Wallace criteria for inactive disease (WID) and clinical remission. Results: The most common reason for withdrawal of previous TOC was secondary ineffectiveness (22 cases, 71%); in 6 cases (19.4%) allergic reaction was observed; in two cases (6.5%) primary non-effectiveness appeared; and in one case (3.2%) there was marked infusion reaction. At CAN initiation, sJIA activity was as follows: 15 (12: 23) for JADAS-71; 45 (36.5: 72) and 58 (45: 81) for physician's and patient's global assessment VAS; and 0.25 (0: 0.62) for the CHAQ disability index. After 12-month treatment, 22 (71%) patients reached WID: 21 on CAN therapy and 1 – after CAN withdrawal due to administrative reason and stable WID. ACR50/70/90 response was achieved by 84.2%/84.2%/64.7% patients in early arthritis group and in 83.3%/75%/75% patients in late arthritis group (p=0.792). However, 42.1% of patients with early sJIA achieved remission in the first 1.5 years without any further relapse during all the studied period and only 16.7% of patients with late arthritis (p=0.239). In multivariable analysis, it was found that age of sJIA onset (OR (2.5-97.5 CI) 0.353 (0.13 - 0.72), p=0.015), number of joints with active arthritis at sJIA onset (2.308 (1.26-5.73), p=0.025), and JADAS-71 at sJIA onset (0.664 (0.44-0.88), p=0.016) were associated with successful treatment with rapid achievement of stable remission. During the 76.7 patient-years follow-up period, 18 of 31 (58.1%) patients were able to achieve a stable clinical remission and 27 (87.1%) – WID. Two patients have achieved successfully drug-off remission. Serious adverse event (SAE) was reported in one (3.2%) patient (enteritis). Conclusion: Long-term canakinumab therapy proved to be effective and safe as a second biologics after tocilizumab for any duration of the disease. However, patients with early arthritis are more likely to quickly achieve stable remission without further relapse. Younger onset of sJIA with polyarthritis involvement and low disease activity are predictors of rapid and stable remission. Disclosure of Interests: Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Elizaveta Krekhova: None declared, Tatyana Dvoryakovskaya: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Evgeniya Chistyakova: None declared, Olga Lomakina: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Dariya Vankova: None declared, Meyri Shingarova: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared, Ivan Kriulin: None declared